Adaptive Inclusion Education Model for Students Mobility Barriers at Karang Jati Elementary School Blora - Tiwan, Nudjedwi Raleg (Juwara: Jurnal Wawasan dan Aksara, 2025)
This study aims to explore an adaptive inclusion education model for students with mobility barriers at SD Karang Jati Blora. Using a descriptive qualitative approach, data was collected through classroom observations, in depth interviews with classroom teachers, Special Assistant Teachers, students, and parents, and field documentation. This study found that inclusive learning strategies are applied through assignment modification, flexibility of evaluation methods, and the active role of Special Assistant Teachers as academic and emotional companions. The findings also showed that students' social interaction with movement barriers took place positively in the classroom, supported by a culture of peer empathy and a non-discriminatory approach to teachers. Parents play an important role in supporting children's learning processes, even though they have not been systemically involved in the preparation of learning. The main challenge facing schools is the absence of specialized training, formal documentation systems such as the Individualized Education Plan, on the role of Special Assistant Teachers. The study recommends the need for more affirmative education policies, ongoing training, and strengthening collaboration between stakeholders to ensure the sustainability of adaptive inclusion practices in primary schools.